2013
DOI: 10.1002/cbin.10219
|View full text |Cite
|
Sign up to set email alerts
|

Periostin and transforming growth factor β‐induced protein (TGFβIp) are both expressed by osteoblasts and osteoclasts

Abstract: Periostin (Postn) and transforming growth factor β-induced protein (TGFβIp) are two closely related extracellular matrix (ECM) proteins predominantly distributed in collagen-rich connective tissues submitted to mechanical strain, including bone and more specifically the periosteum. We have investigated the expression of Postn and TGFβIp mRNA by primary osteoblasts isolated from mouse periosteum and calvaria, or by the osteoblast-like MC3T3-E1 cell line, and by osteoclasts from mouse long bones differentiated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Increase in MMP has been previously associated with osteocytic osteolysis, but this has been seen only in real microgravity condition (space shuttle mission) [34]. Secondly, periostin could have a direct role on osteoclasts as suggested by in vitro studies [35][36][37]; however, to our knowledge this effect has never been demonstrated in vivo. In a previous study, we did not detect an effect of periostin deficiency on osteoclast numbers, surface or markers of bone resorption either in intact or ovariectomized mice [38].…”
Section: Discussionmentioning
confidence: 85%
“…Increase in MMP has been previously associated with osteocytic osteolysis, but this has been seen only in real microgravity condition (space shuttle mission) [34]. Secondly, periostin could have a direct role on osteoclasts as suggested by in vitro studies [35][36][37]; however, to our knowledge this effect has never been demonstrated in vivo. In a previous study, we did not detect an effect of periostin deficiency on osteoclast numbers, surface or markers of bone resorption either in intact or ovariectomized mice [38].…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, POSTN is involved in regulating the Wnt signaling pathway which is an important regulator of both bone and joint metabolism 16,32 . We also showed recently that POSTN is not only expressed in osteoblasts but also in osteoclasts from mouse long bones differentiated in vitro 35 .…”
Section: Table IIImentioning
confidence: 92%
“…However, in bone cells, periostin and βig-h3 are expressed in both osteoblasts and osteoclasts in vitro (Merie et al 2014), suggesting that both genes possibly act cooperatively in bone formation. By contrast, after myocardial inside : collagen cross-linking outside: cell migraƟon Fig.…”
Section: Periostin Paralogue Tgfbi (βIg-h3)mentioning
confidence: 99%